Analysis of temperature profile on a PCB in the preheat section of a wave soldering process - Hoe, Swee Long. (2008)
In the Printed Circuit Board Assembly Industry, a well defined temperature profile in the preheat section of a wave soldering machine is essential for good solderability, quality and product reliability. A proper preheat to PCB and electronic components will eliminate defects due to thermal shock, poor soldering joints and unreliable leads connection. In practice, this proper preheat profile is achieved through a time consuming trial-and-error method and years of experience in wave soldering process control.